EXCELLENT SPORTS OF NORTH SULAWESI - Tangkudung, James; Puspitorini, Wahyuningtyas (Program Pascasarjana Universitas Negeri Jakarta, 2016)
The purpose of this research is to know which sports are excellent in North Sulawesi, hence it is necessary to conduct a study regarding sports which can be excellent to decide the development priority policies of North Sulawesi in the future North Sulawesi is one of the provinces which has different characteristics of demography and socio-culture with different Provinces For that background above, either formal or rational juridical basis, the researcher is interested to conduct the excellent sports study in North Sulawesi. The focus of this study is âexcellent sports in North Sulawesi . Etnografi method and kualitatif approach by applying Miles and Huberment model.The results of this research like as (1) Area potential; (2) Human Resources (HR); (3) Facilities and Infrastructure; (4) Competition; (5) Funding; and (6) Performances.